2020
DOI: 10.1021/acs.iecr.9b06206
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Bi2O3 Surface-Modified Polyvinylidene Fluoride Membrane via an Ultraviolet Photografting Method: Improving Hydrophilicity and Degree of Acrylic Acid Grafting

Abstract: In this study, a superior hydrophilic polyvinylidene fluoride (PVDF) membrane with an enhanced monomer grafting ratio was prepared via an ultraviolet (UV) photografting polymerization method. The water contact angle (WCA) of the Bi 2 O 3 −acrylic acid (AA)-modified PVDF membrane reduces to 40.4°with the increasing of Bi 2 O 3 content, illustrating significant enhancement of membrane hydrophilicity. Attenuated total reflection Fourier transform infrared spectra and atomic absorption spectroscopy reveal that Bi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…ROS Identification. As studies have shown that the catalytic oxidation of organic dyes depends strongly on the action of highly reactive ROS that may be generated by oxygen activation, 38 radical scavenging experiments were combined with EPR spintrapping techniques in this study to detect ROS formed during the process of catalytic oxidation. TBA (100 mM), p-BQ (10 mM), and L-histidine (50 mM) were used as scavengers of •OH, •O 2 − , and 1 O 2 , respectively, 57 to determine the relative contributions of different ROS to the catalytic degradation of pollutants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ROS Identification. As studies have shown that the catalytic oxidation of organic dyes depends strongly on the action of highly reactive ROS that may be generated by oxygen activation, 38 radical scavenging experiments were combined with EPR spintrapping techniques in this study to detect ROS formed during the process of catalytic oxidation. TBA (100 mM), p-BQ (10 mM), and L-histidine (50 mM) were used as scavengers of •OH, •O 2 − , and 1 O 2 , respectively, 57 to determine the relative contributions of different ROS to the catalytic degradation of pollutants.…”
Section: Resultsmentioning
confidence: 99%
“…The CuNi–C grafting process is illustrated in Scheme and includes PVDF membrane surface carboxylation, catalyst handling and deposition, and thermal cross-linking. , PVDF membranes were ultrasonically cleaned with an ethanol–water solution to remove surface impurities and adhered organic contaminants and subsequently dried. Acrylic acid was grafted onto the PVDF membrane surface by dip-coating and ultraviolet (UV) grafting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, UV photo-grafting method has the advantages of low cost and easy continuous process compared to one of the conventional coating methods, plasma polymerization process, which usually includes the vacuum process. Moreover, numerous materials can be grafted through UV photo-grafting, [30][31][32][33] with zwitterionic polymer grafting being a typical application. For instance, a polysulfobetaine methacrylate (PSBMA) brush was grafted onto a PVDF membrane to enhance its ultrafiltration performance.…”
Section: Introductionmentioning
confidence: 99%
“…Ultraviolet (UV)-induced Cu(II)-mediated reversible deactivation radical polymerization (RDRP) is an environmentally friendly synthesis technology which combines UV stimulation and Cu(II)-mediated RDRP (Chuang et al 2014;Hu et al 2018aHu et al , 2018b. UV-induced Cu(II)-mediated RDRP can be used to modify pure PVDF membranes as it enables a more compact combination of hydrophobic and hydrophilic chains to ensure that the hydrophilic chain is fixed on the surface of the PVDF membranes (Cui et al 2019;Zou et al 2020;Li et al 2021). Therefore, the addition of amphiphilic copolymers to PVDF membranes can improve the hydrophilicity and antifouling properties.…”
Section: Introductionmentioning
confidence: 99%